Allocation problems with indivisibilities when preferences are single-peaked - Carmen Herrero; Ricardo Martínez (SERIEs - Journal of the Spanish Economic Association, 2011)
We consider allocation problemswith indivisible goods when preferences are single-peaked. In this paper we identify the family of efficient, non-manipulable, consistent, and balanced solutions. We refer those solutions as Temporary Satisfaction Methods, that can be viewed as extensions to the indivisible case of the so-called uniform rule.
Keywords: D61; D63; D74; 330; allocation problem; indivisibilities; single-peaked preferences; priority standard; temporary satisfaction methods; Allokationseffizienz; Präferenztheorie; Unteilbarkeit